Student-Centered Learning to Improve Character Education in High School Economics Learning: The Mediating Role of Economic Literacy - Fahimul Amri; Diah Dinaloni; Nufan Balafif (Journal of Economic Education and Entrepreneurship Studies, 2026)
The background of this research is that the development of economic literacy and character education in students has become a primary goal of economics education, including in secondary schools. Although SCL has been widely recognized as an effective pedagogical approach, empirical evidence explaining how SCL contributes to character education through economic literacy is still limited, particularly in secondary school economics education. This study aims to examine the effect of SCL on economic literacy and character education in students, as well as the role of economic literacy as a mediating variable. The method used a quantitative approach. Data were collected from 249 high school students in three schools in East Java. The sampling technique used was simple random sampling. The instrument used a questionnaire with a Likert scale. Data analysis used PLS-SEM. The results showed that SCL has a positive effect on economic literacy; SCL has a direct positive effect on character education (β = 0.120); economic literacy positively affects character education; and economic literacy mediates the effect of SCL on character education (β = 0.064). The Conclusion indicates that SCL improves student character both directly and indirectly through the mediation of economic literacy. This study highlights the importance of integrating student-centered economic learning to improve economic literacy and student character. The theoretical implications of this research extend constructivist learning theory by identifying economic literacy as an important mediating mechanism linking SCL to student character development. The practical implications of this study are for economics teachers and curriculum developers seeking to integrate SCL with economic literacy to promote character among secondary school students.